Relationships between general and specific physical characteristics and match-related indicators in elite Finnish ice hockey players at different playing positions - Korte, Ville (2020)
One of the challenges in ice hockey is understanding the differences in physical characteristics between players of different rink playing positions. In game situations, differences are obvious mainly because of tactical elements of game activities. Differences have occurred by various on-ice and off-ice tests of which many have correlated with each other. For example, general and specific speed and power tests have showed significant relationships whereas only low correlations between endurance tests. Only a few authors have investigated association between strength and on-ice performance showing contradictory results. Regardless of the lack of research in this area, authors have observed high-intensity performance during game correlating with cardiovascular loading in submaximal Yo-Yo intermittent recovery ice hockey tests, level 1 (Yo IR1-IHSUB). The aim of this study was to examine the relationships between on- and off-ice tests and match-related indicators. The second aim was to investigate differences between forwards and defensemen in general and specific physical qualities and match-related activities. The male subjects were recruited from five different teams and played elite level ice hockey in Finland (n = 140). Four of teams represented Finnish Elite Ice Hockey League and one of the teams was Finnish U20 Ice Hockey League team. The measurements were executed in fall 2019. General tests included anthropometric measurements, 30-metre running speed test with 5- and 10-metre splits, countermovement jump (CMJ) and CMJ with extra loads (20, 40 and 60 kg), pro agility (5-10-5-m) off-ice test (CODRUN), Wingate test and incremental cycle ergometer test. Specific tests consisted of 30-metre skating speed test with 5- and 10-metre splits, pro agility (5-10-5-m) on-ice test (CODICE) and maximal Yo-Yo intermittent recovery ice hockey tests, level 1 (Yo IR1-IH). Bitwise corporation provided match-related data including playing time, covered distance, number of shifts, playing time per shift, average speed and maximal speed. No differences were found between forwards and defensemen in any off-ice and on-ice variables (p > 0.05). However, differences were obvious in match-related indicators. Defenders spent more time on ice (16:35 vs. 14:39 min) and still, had higher playing time per shift (0:47 vs. 0:44 min) even though no significant differences in number of shifts. The forward players’ maximal speed and average speed were significantly higher than that of defensemen (p > 0.001, both). Especially, speed-power tests showed significant correlations with on-ice tests. CMJ without load and with extra loads had highest association with on-ice performance, showing correlations with all on-ice power tests (r= -0.380 - -0.686, p < 0.01). VO2max correlated with distance in Yo IR1-IH (r = 0.514, p < 0.01). Only some, but mainly low correlations occurred between tests and match-related indicators. The nature of the sports of ice hockey, such as tactical aspects and roles of players may affect significantly to relationships between physical qualities and match activities. Consequently, it cannot be argued that physical characteristics would not play a decisive role in the game of ice hockey. However, coaches and trainers should be aware of what tests to use to assess players’ performance on-ice. Especially speed-power tests are usable tools to assess on-ice performance. However, it seems that body composition of players does not affect significantly to on-ice performance. According to this study, positional differences do not occur in physical qualities but do appear in game activities. Due to these findings, coaches should focus more to develop physical performance corresponding with positional demands in match activities.